Clinician Ratings of Interpreter Mediated Visits in Underserved Primary Care Settings with Ad hoc, In-person Professional, and Video Conferencing Modes - Nápoles, Anna M. (2010)
Language interpretation ameliorates health disparities among underserved limited English-proficient patients, yet few studies have compared clinician satisfaction with these services. Self-administered clinician post-visit surveys compared the quality of interpretation and communication, visit satisfaction, degree of patient engagement, and cultural competence of visits using untrained people acting as interpreters (ad hoc), in-person professional, or video conferencing professional interpretation for 283 visits. Adjusting for clinician and patient characteristics, the quality of interpretation of in-person and video conferencing modes were rated similarly (OR=1.79; 95% CI 0.74, 4.33). The quality of in-person (OR=5.55; 95% CI 1.50, 20.51) and video conferencing (OR=3.10; 95% CI 1.16, 8.31) were rated higher than ad hoc interpretation. Self-assessed cultural competence was better for in-person versus video conferencing interpretation (OR=2.32; 95% CI 1.11, 4.86). Video conferencing interpretation increases access without compromising quality, but cultural nuances may be better addressed by in-person interpreters. Professional interpretation is superior to ad hoc (OR=4.15; 95% CI 1.43, 12.09).